2012
DOI: 10.1177/1477370811424383
|View full text |Cite
|
Sign up to set email alerts
|

Gender framing effects in victim surveys

Abstract: Crime victimization surveys are important sources of trend information and provide data for basic criminological research. In recent years, victim surveys have proliferated and their strengths are well known. The aim of this study is to increase the methodological literature on victim surveys by analysing framing effects, defined as the way the survey instrument communicates its topic and aim, especially in terms of the gendered nature of violence. Three experimental frames were applied to independent, random … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The method has been used by Nordics in intervention evaluation (Balvig & Holmberg 2011;Kjaer Minke 2011) and methodological analysis (Kivivuori et al 2013). Designs comparing independent random samples, which is admittedly not the same as randomisation, have been used to study the effects of researcher-controlled stimuli related to punitivity research (Jerre & Tham 2010) and methods development (Kivivuori et al 2012). …”
Section: Editorial Experimental Research In Nordic Criminologymentioning
confidence: 99%
“…The method has been used by Nordics in intervention evaluation (Balvig & Holmberg 2011;Kjaer Minke 2011) and methodological analysis (Kivivuori et al 2013). Designs comparing independent random samples, which is admittedly not the same as randomisation, have been used to study the effects of researcher-controlled stimuli related to punitivity research (Jerre & Tham 2010) and methods development (Kivivuori et al 2012). …”
Section: Editorial Experimental Research In Nordic Criminologymentioning
confidence: 99%
“…First, surveys focused on the topics of crime and security may appeal to different types of people than surveys focused on issues relating to health, thus affecting the composition of the two samples. Second, the choice of framing – ‘defined as the way the survey instrument communicates its topic and aim’ (Kivivouri et al, 2012) – may influence how people respond to particular questions: people recruited into crime surveys are more likely to interpret all questions in relation to criminal activity, even if the question itself does not make explicit reference to crime. Considering both influences, Kivivouri et al (2012) demonstrate the importance of gender framing in victim surveys.…”
Section: Possible Reasons For the Observed Differences Between Surveysmentioning
confidence: 99%
“…Second, the choice of framing – ‘defined as the way the survey instrument communicates its topic and aim’ (Kivivouri et al, 2012) – may influence how people respond to particular questions: people recruited into crime surveys are more likely to interpret all questions in relation to criminal activity, even if the question itself does not make explicit reference to crime. Considering both influences, Kivivouri et al (2012) demonstrate the importance of gender framing in victim surveys. Comparing self-reported victimization estimates when the survey was framed around male-to-male violence, female-to-male violence and male-to-female violence, they find that the male-to-female violence frame invokes both the highest response rate and the highest reporting rate among women.…”
Section: Possible Reasons For the Observed Differences Between Surveysmentioning
confidence: 99%
“…However, the bulk of the studies have been carried out in the US and there is a lack of research that uses police-recorded crime as a measure of criminality, because many studies resort to either survey-based measures of crime and disorder or use extreme forms of aggression such as homicides as a measure of neighbourhood violence. Although there are well-known shortcomings in police-recorded crime data, survey-based measures also suffer from inaccuracy owing to, for example, unequal non-response and frame effects (Hart et al, 2005;Kivivuori et al, 2012;Laaksonen and Heiskanen, 2014). Sampson and Groves (1989) employed a survey-based study utilizing data from the British Crime Survey, using local friendship networks, organizational participation and youth supervision as predictors of violent crime victimization, and found that communities characterized by sparse friendship networks, unsupervised teenage peer groups and low organizational participation had disproportionately high rates of crime and delinquency.…”
Section: Previous Research On Collective Efficacy and Crimementioning
confidence: 99%